The association between adverse pregnancy outcomes and maternal factor V Leiden genotype: a meta-analysis - Dudding, Tracy E.; Attia, John (Thrombosis and Haemostasis, 2004)
The conclusions of studies to date which evaluate a possible association between factor V Leiden and adverse pregnancy outcome have been conflicting. This study was undertaken to further investigate this association. Our objective was to evaluate the association between adverse pregnancy outcomes and maternal factor V Leiden genotype by meta-analysis. Inclusion criteria were: (a) cohort or case control design; (b) outcomes clearly defined as one of the following: first or second/ third trimester miscarriage or intrauterine death, preeclampsia, fetal growth retardation, or placental abruption; (c) both the case and control mothers tested for the factor V Leiden mutation; (d) sufficient data for calculation of an odds ratio. Both fixed and random effect models were used to pool results and heterogeneity and publication bias were checked. For first trimester fetal loss, the pooled odds ratio was heterogeneous (p=0.06) and no dose-response curve could be found. For second/third trimester fetal loss, there was a consistent and graded increase in risk: the odds ratio was 2.4 (95% CI 1.1-5.2) for isolated (non-recurrent) third trimester fetal loss, rising to 10.7 (95% CI 4.0-28.5) for those with 2 or more second/third trimester fetal losses. FactorV Leiden is associated with a 2.9 fold (95% CI 2.0-4.3) increased risk of severe preeclampsia, and a 4.8 fold (95% CI 2.4-9.4) increased risk of fetal growth retardation. These results support factor V Leiden testing for women with recurrent fetal loss in the second/third trimester. Women with only 1 event may also warrant testing if the fetal loss occurred in the third trimester. Conversely, in those women known to have the factor V Leiden mutation, monitoring for adverse pregnancy outcomes is warranted; whether this means increased vigilance or anti-coagulant prophylaxis is still contentious.
Keywords: Factor V Leiden; fetal death; intrauterine growth retardation; preeclampsia; pregnancy; meta-analysis